2014
DOI: 10.1155/2014/671795
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Early-Age Crack of Mass Concrete under the Controlled Temperature History

Abstract: Thermal deformation under restrained conditions often leads to early-age cracking and durability problems in mass concrete structures. It is crucial to monitor accurately the evolution of temperature and thermal stresses. In this paper, experimental studies using temperature stress testing machine (TSTM) are carried out to monitor the generated thermal cracking in mass concrete. Firstly, components and working principle of TSTM were introduced. Cracking temperatures and stress reserves are selected as the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Engineering experience indicates that the difficulty in avoiding cracks is due to insufficient understanding of the mechanism of crack formation, the randomness of hydrometeorological conditions, and the failure of material parameters in reflecting actual engineering conditions; in addition, crack formation occurs because of the absence of timely and reasonable measures for temperature control that are tailored to the actual conditions of specific projects. [8][9][10][11][12][13] Therefore, in the current condition in which a major breakthrough in the theory of temperature control is difficult to achieve, [14][15][16][17][18][19][20][21][22][23][24] crack prevention should still be focused on the selection of timely and reasonable measures for temperature control.…”
Section: Forewordmentioning
confidence: 99%
“…Engineering experience indicates that the difficulty in avoiding cracks is due to insufficient understanding of the mechanism of crack formation, the randomness of hydrometeorological conditions, and the failure of material parameters in reflecting actual engineering conditions; in addition, crack formation occurs because of the absence of timely and reasonable measures for temperature control that are tailored to the actual conditions of specific projects. [8][9][10][11][12][13] Therefore, in the current condition in which a major breakthrough in the theory of temperature control is difficult to achieve, [14][15][16][17][18][19][20][21][22][23][24] crack prevention should still be focused on the selection of timely and reasonable measures for temperature control.…”
Section: Forewordmentioning
confidence: 99%
“…The phenomena of autogenous shrinkage induced cracking are considered in [8] for high-performance concrete, in [9] for slag cement concretes, and in [10][11][12][13] for fiber reinforced concrete. More recently, the research contribution in this field often focuses on early-age hygro-thermo-chemo-mechanical behaviors [14][15][16][17][18][19][20][21][22]. The state-of-the-art numerical models studying early-age behavior in concrete is mainly based on the hygro-thermo-chemo-mechanical coupled framework [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Both the calculations and experiments show that reinforcement can postpone the occurrence of the appearance of the first major crack and can enhance the ultimate tensile strain of the structure (Shi et al, 2014;Sule, 2003). In terms of temperature strains, this would mean that an additional temperature difference of up to 10.8 K could be accommodated (Sule and van Breugel, 2004).…”
Section: Design Of Reinforcement To Control Crackingmentioning
confidence: 96%
“…It has been shown that controlling the temperature is an effective way to prevent or reduce the risk of crack formation in concrete. Under slow cooling conditions, concrete can undergo a 20 K drop in temperature without cracking (Neville, 2011;Shi et al, 2014;Bobko et al, 2015). Early-age cracking occurs when the tensile strain that arises either from restrained thermal contractions or temperature differentials within a concrete section exceeds the actual tensile strain capacity of the concrete (Bamforth, 2007;Carino and Clifton, 1995;Mihashi and Leite, 2004).…”
Section: Introductionmentioning
confidence: 99%